Development of a vaccine against salmon louse (Lepeophtheirus salmonis) - Midtbø, Elisabeth Andrea (The University of Bergen, 2023)
Aquaculture is a growing industry whilst facing a major problem, the ectoparasite Lepeophtheirus salmonis. Parasite control in 2015 was estimated to cost 5 billion NOK. The challenges with the parasite are complex, and the infestations have previously been controlled with different kinds of chemical treatments. However, due to increasing resistance against existing treatments and the concern against harming non-target organisms, alternative treatment methods are needed. A vaccine against the parasite would be a cost-effective way to handle the infestation, though; several years of research have not uncovered an effective vaccine against the parasite. Currently, there is only one existing vaccine against ectoparasites. This vaccine is direct toward ticks, Boophilus microplus, in the cattle industry. A concealed antigen in the tick gut was used to develop a vaccine that resulted in lower fecundity. The Mesh protein is a membrane protein involved in the formation of septate junctions in the gut of Drosophila. The protein was identified as potential vaccine candidate by the SLRC, where knockdown with RNAi resulted in a deformed gut in the louse and high rates of mortality. In the present study Mesh transcripts were confirmed to be localized in the intestine of L. salmonis. A recombinant Mesh protein was produced, incorporated into a vaccine and injected in Atlantic salmon. The trial fish were subjected to an infestation with copepodids, and the immune response was assessed at the end of the trial. No differences were detected in lice numbers post immunization, but an elevated immune response was detected in the vaccinated salmon. Masteroppgåve i fiskehelse MAMN-FISK FISK399